Evaluation of Physical Education Program Sports and Health Material Activities in Water at Junior High School - Risman, Iqbal; Argantos, Argantos; Aziz, Ishak; Welis, Wilda; Zarya, Fiky (Department of Physical Education, Sport, Health and Recreation, 2023)
This study aims to determine the implementation of the physical education learning program for sports and water activities at Junior High School 14 Pekanbaru using an evaluation approach to the Context, Input, Process, Product, and Outcome (CIPP) model. The subjects of this study were the principal, and (SPEH) teachers, and students. Data collection is done by Documentation, Observation, and Interview. Descriptive analysis data were analyzed by qualitative descriptive technique. The results showed that the evaluation of the context, the learning materials used were relevant to the 2013 curriculum, but the technical implementation was not carried out as a whole; The input shows the educational background of the teacher in accordance with the qualifications of the SPEH teacher and the background of the students being able to carry out learning, the SPEH infrastructure facilities that support activities in the water are not provided by the school. The process includes the implementation of SPEH learning that has been going quite well; The product of student learning outcomes and the average class value are in the good enough category; Outcome is the impact on students the importance of learning PJOK for health and daily life. In general, the learning program has been guided by (BSNP), but not yet fully in accordance with national education standards, which include conformity with the implementation of learning with the delivered lesson plans, PJOK facilities and infrastructure, water activity materials are still inadequate, as well as the implementation and method of giving SPEH learning scores. also not up to standard